2007
DOI: 10.1074/jbc.m604327200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Nitric Oxide Dynamics and Affinity with Alcaligenes xylosoxidans Cytochrome c´

Abstract: The bacterial heme protein cytochrome c from Alcaligenes xylosoxidans (AXCP) reacts with nitric oxide (NO) to form a 5-coordinate ferrous nitrosyl heme complex. The crystal structure of ferrous nitrosyl AXCP has previously revealed that NO is bound in an unprecedented manner on the proximal side of the heme. To understand how the protein structure of AXCP controls NO dynamics, we performed absorption and Raman timeresolved studies at the heme level as well as a molecular computational dynamics study at the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
44
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 51 publications
11
44
1
Order By: Relevance
“…It must be emphasized that because the NO geminate recombination to the 4c heme is ultrafast (τ gem = 7.5 ps), numerous cycles of photodissociation/recombination can occur for the same molecules during the 6-ns pulse used. This phenomenon, already observed for cytochrome c′ (28,33), results in a higher apparent dissociation yield so that kinetics in subsequent decades appear with a higher amplitude relative to the initial peak than in measurements using a femtosecond excitation pulse (Fig. 2C).…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…It must be emphasized that because the NO geminate recombination to the 4c heme is ultrafast (τ gem = 7.5 ps), numerous cycles of photodissociation/recombination can occur for the same molecules during the 6-ns pulse used. This phenomenon, already observed for cytochrome c′ (28,33), results in a higher apparent dissociation yield so that kinetics in subsequent decades appear with a higher amplitude relative to the initial peak than in measurements using a femtosecond excitation pulse (Fig. 2C).…”
Section: Resultssupporting
confidence: 58%
“…The dissociation of NO yields a 4c heme, as observed by the bleaching at 397 nm (Fig. 2B) to which NO geminately rebinds without energy barrier from within the heme pocket with τ gem = 7.5 ps (25,26), a property observed in other 4c heme proteins (28,29). Accordingly, the induced absorption centered at 428 nm due to the 4c heme decreases rapidly, and a new maximum appears, centered at 433 nm, meaning that a second species was formed and decays more slowly.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…If the structural conformation of the heme domain is not strictly the same for full-length protein versus isolated domain, then the diatomic ligand dynamics will be modified. It is established that the dynamics of a diatomic ligand within the protein core is highly sensitive to the heme pocket conformation and to strains on the heme iron through the proximal histidine, which imposes energy barriers to diatomic motion (15)(16)(17). Here, we compared the dynamic interaction of NO and CO within the full-length sGC and the isolated human heme domain of the ␤ 1 -subunit, restricted to the first 190 amino acids, referred to as ␤ 1 (190) hereafter.…”
Section: ؊1 ⅐Smentioning
confidence: 99%
“…This is demonstrated by the high proportion of geminate recombination after excitation (~ 99%) on an ultrafast time scale (τ = 7 ps) 18. Laser‐flash photolysis studies have shown that only ~ 1% of the population releases NO to the surrounding bulk solvent, with rebinding of the proximal histidine to the heme Fe 20.…”
Section: Introductionmentioning
confidence: 99%